2009
DOI: 10.1159/000206143
|View full text |Cite
|
Sign up to set email alerts
|

Role of Translocation of Pathogen-Associated Molecular Patterns in Sepsis

Abstract: Background/Aim: Unlike animals, the incidence of bacterial translocation and its clinical significance remain to be determined in humans, which may be due to the lack of accurate methods to confirm and monitor bacterial translocation. The literature on the consequences of novel insights of bacterial translocation was reviewed. Methods: The Medline databases were searched for publications regarding translocation of bacteria as well as pathogen-associated molecular patterns. Results: Although substantial data su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 106 publications
0
13
0
4
Order By: Relevance
“…In our study, gram-negative bacteraemia was observed in 19/55 (35%) of patients with an ЕАА < 0.6 and only in 11/26 (42%) of cases with an ЕАА ≥ 0.6, which may reflect the load from other sources, mainly the gut [12]. …”
Section: Discussionmentioning
confidence: 99%
“…In our study, gram-negative bacteraemia was observed in 19/55 (35%) of patients with an ЕАА < 0.6 and only in 11/26 (42%) of cases with an ЕАА ≥ 0.6, which may reflect the load from other sources, mainly the gut [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Whether bacterial translocation has any clinical importance in humans remains controversial [12,13], possibly due to the lack of accurate methods for confirming and monitoring the translocation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the translocation of MAMPs, viable bacteria can cross the gut endothelial barrier through a process known as bacterial translocation. Once considered a controversial topic, bacterial translocation is now a well-recognized phenomenon (44,45) . In individuals with a normal immune system, bacterial translocation is rare, but in disease states, gut inflammation can increase intestinal permeability allowing more bacteria to cross the endothelial barrier (46) .…”
Section: How the Gut Microbiome Affects Distant Organsmentioning
confidence: 99%